O retorno de mercado das companhias abertas brasileiras baseadas em intangíveis - Oliveira, Camila Gandini de (Universidade do Vale do Rio dos Sinos, 2022)
The intense competition among companies is forcing them to become different from their competitors in the face of globalization and advances in information technology. These economic forces are related to the growing interest in the subject of intangible assets, such as brand, patent, and intellectual capital, which, for example, are unique assets, whose peculiarities may allow differentiation among other companies. In this sense, national and international authors have intensified research on intangible assets, and found that the generation of wealth of these companies would be directly linked to their intangible assets. The research aimed to analyze which are the impacts of Fama and French’s model (2015) on the stock returns of Brazilian companies based on intangible assets. To answer the research objective, data were collected from companies listed on B3 between 2010 and 2021. Given the collection carried out, the sample was analyzed and classified, according to the interest of this research, which is to study only the companies based on intangibles, thus obtaining at the end the sample of 69 Brazilian companies. To test the research hypotheses, the regression model with panel data was used, as used by the original authors. The five-factor model was applied with adaptations to the characteristics of the Brazilian market, to analyze the relevance of each factor and its explanatory power, for the return of the sample composed of 69 companies, which were classified as being based on intangibles. Among the results found, three factors proved to be significant: MRP (Market Risk Premium), which represents the market factor, the HML (High minus Low) factor, which represents the Book-to-Market index, and the RMW factor (Robust minus Weak), which represents the level of profitability of the company. This indicates that these three factors, MRP, HML and RMW have the greatest impact on the return of these companies specifically. These results are in line with previous research, however the sample set in this study is different from that performed in previous studies. The results of this research contribute to the literature and to academia by performing the classification of companies based on intangibles, and also contribute to the field of finance by showing that the five-factor model has explanatory power over the return of these companies.
Keywords: Ativos intangíveis; Retorno; Modelo de Cinco Fatores de Fama e French; Intangible assets; Return; Five-Factor Model of Fama and French; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis